Colonic Leucine-Rich Repeat Kinase 2 Expression Is Increased and Associated With Disease Severity in Patients With Parkinson’s Disease - Liao, Peng-Hsiang; Chiang, Han-Lin; Shun, Chia-Tung; Hang, Jen-Fan; Chiu, Han-Mo; Wu, Ming-Shiang; Lin, Chin-Hsien (Frontiers in Aging Neuroscience, 2022)
Background: Mutations in leucine-rich repeat kinase 2 (LRRK2) comprise a common genetic risk factor for Parkinson’s disease (PD) and inflammatory bowel disease. We investigated the expression of LRRK2 in colonic biopsies obtained from a cohort of PD patients and healthy controls. Methods: A cohort of 51 PD patients and 40 age- and gender-matched controls who have colonic biopsied samples were recruited. Among these participants, 26 individuals (12 PD patients and 14 controls) had a series of colon biopsies. For the patients with PD, the first biopsies were taken before the PD diagnosis. The colonic expression of LRRK2 was assayed by immunohistochemical staining. Results: The fraction of LRRK2-positive cells among the total cell count in biopsied colonic tissues was significantly higher in PD patients than controls (0.81%±0.53% vs. 0.45%±0.39%; P=0.02). Colonic LRRK2 immunoreactivity was higher in those with LRRK2 genetic variants compared to those with wild type LRRK2 (2.44%±1.15% vs. 0.21±0.13%, P<0.01). Age had no effect on LRRK2 expression (P=0.96). LRRK2 expression correlated with disease severity in regards to motor symptoms measured by the UPDRS part III scores (r=6335, P<0.001) and cognitive dysfunction measured by the mini-mental status examination scores (r=-0.5774, P<0.001). PD patients in the prodromal phase had a steeper increase in colonic LRRK2 expression compared to controls during the serial colon biopsy assessment (P<0.01). Conclusions: Colonic LRRK2 expression was increased in PD patients compared to controls, and the expression level correlated with disease severity.